Pathological Features of Mitochondrial Ultrastructure Predict Susceptibility to Post-TIPS Hepatic Encephalopathy - Hong-bin Li; Zhen-dong Yue; Hong-wei Zhao; Lei Wang; Zhen-hua Fan; Fu-liang He; Xiao-qun Dong; Fu-quan Liu (Canadian Journal of Gastroenterology and Hepatology)
Background. Post-TIPS hepatic encephalopathy (PSE) is a complex process involving numerous risk factors; the root cause is unclear, but an elevation of blood ammonia due to portosystemic shunt and metabolic disorders in hepatocytes has been proposed as an important risk factor. Aims. The aim of this study was to investigate the impact of pathological features of mitochondrial ultrastructure on PSE via transjugular liver biopsy at TIPS implantation. Methods. We evaluated the pathological damage of mitochondrial ultrastructure on recruited patients by the Flameng classification system. A score ≤2 (no or low damage) was defined as group A, and a score >2 (high damage level) was defined as group B; routine follow-up was required at 1 and 2 years; the incidence of PSE and multiple clinical data were recorded. Results. A total of 78 cases in group A and 42 in group B completed the study. The incidence of PSE after 1 and 2 years in group B (35.7% and 45.2%, respectively) was significantly higher than that in group A (16.7% and 24.4%, respectively); the 1- and 2-year OR (95% CI) were 2.778 (1.166-6.615) and 2.565 (1.155-5.696), respectively, for groups A and B. Importantly, group B had worse incidence of PSE than group A [P=0.014, hazard ratio (95%CI): 2.172 (1.190-4.678)]. Conclusion. Aggressive damage to mitochondrial ultrastructure in liver shunt predicts susceptibility to PSE. The registration number is NCT02540382.